2021
DOI: 10.1242/jeb.242939
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution of skin surface microarchitecture and increased skin hydrophobicity in semi-aquatic anole lizards

Abstract: Animals that habitually cross the boundary between water and land face specific challenges with respect to locomotion, respiration, insulation, fouling and waterproofing. Many semi-aquatic invertebrates and plants have developed complex surface microstructures with water-repellent properties to overcome these problems, but equivalent adaptations of the skin have not been reported for vertebrates that encounter similar environmental challenges. Here, we document the first evidence of evolutionary convergence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 110 publications
0
1
0
Order By: Relevance
“…Having shown that mammals and birds share a TRPM8-dependent shaking behavior, the question naturally arises as to how this behavior evolved – is it conserved, or did it evolve at least twice? The most recent common ancestor of mammals and birds – an early amniote – had no capacity for axial twisting of the thoracic spine (38, 39) and probably no need to shake, as it likely had a self-cleaning hydrophobic integument, as some modern lizards (40, 41). On the other hand, it likely already took advantage of TRPM8’s sensitivity to cold, which was acquired as the first tetrapods emerged, long before hairs and feathers evolved (42).…”
Section: Discussionmentioning
confidence: 99%
“…Having shown that mammals and birds share a TRPM8-dependent shaking behavior, the question naturally arises as to how this behavior evolved – is it conserved, or did it evolve at least twice? The most recent common ancestor of mammals and birds – an early amniote – had no capacity for axial twisting of the thoracic spine (38, 39) and probably no need to shake, as it likely had a self-cleaning hydrophobic integument, as some modern lizards (40, 41). On the other hand, it likely already took advantage of TRPM8’s sensitivity to cold, which was acquired as the first tetrapods emerged, long before hairs and feathers evolved (42).…”
Section: Discussionmentioning
confidence: 99%
“…Complementary insights into convergent evolution have emerged from a dramatic expansion of phylogenetic comparative investigation to examine scalation, claw morphology, physiology, display behavior, and diving (Muñoz et al 2014, Wegener et al 2014, Gunderson et al 2018, Salazar et al 2019, Yuan et al 2019, Baeckens et al 2021, Boccia et al 2021, Ord et al 2021. Such work revealed iterated convergence in a remarkable behavior that had gone unnoticed by earlier generations of anole biologists-underwater rebreathing in semiaquatic anoles (Boccia et al 2021) (Figure 5).…”
Section: Repeatability Is Common In Macroevolution But Not Universalmentioning
confidence: 99%
“…Each model was run for 5,000,000 iterations with a 1000 burn-in (as in e.g. Baeckens et al 2021). Chains were sampled every 500 iterations.…”
Section: Absolute Sensitivitymentioning
confidence: 99%